Gastrointestinal parasites in wild yellow-tailed woolly monkey (Lagothrix flavicauda) in the Corosha district, Amazonas, Peru - Reátegui Guzmán, Erick H. (2020)
The aim of this study was to identify gastrointestinal parasites present in wild yellow-tailed woolly monkey (Lagothrix flavicauda) in the Corosha district, Amazonas department, Peru. Twenty fecal samples were collected immediately after defecation. Each sample was separated into two portions to be fixed in 10% formalin at 65 ºC and in polyvinyl alcohol (PVA). The samples were analyzed using the Direct, Ritchie, Sheather Sugar, Gomori trichrome staining and modified Ziehl-Neelsen staining methods. The gastrointestinal parasites found were four nematodes (Capillaria sp, Ancylostoma sp, Strongyloides cebus, Strongyloides sp), one cestode (Paratriotaenia oedipomidatis), one acantocephalus (Prosthenorchis elegans) and three protozoa (Entamoeba coli, Cryptosporidium sp, Coccidia sp. Coccidia sp is a new genus reported for Lagothrix flavicauda.